PERBANDINGAN LATIHAN MENGGUNAKAN RESISTANCE BANDS DAN BEBAN DEMPEL TERHADAP KECEPATAN TENDANGAN DEPAN PENCAK SILAT - Oktaviany, Siti Anisah; Muhtar, Tatang; Alif, Muhammad Nur (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to compare and identify training aids that are more effective in increasing the front kick speed of martial artists at SMAN 1 Sumber. The method used in this research is quantitative in the form of an experiment. The design used is the Two Group Pretest-Posttest Design which is used to determine the object being studied before and after being treated. This research uses a saturated sample, where the entire population is involved. The measuring tool used in this research is front kick speed. Data analysis and hypothesis testing used in this research is by using the t-test analysis technique. The results of the research show that there is a significant effect of training using Resistance Bands and Dempel Loads on the speed of front kicks at SMAN 1 Sumber silat with a respective Sig value (2-tailed) of 0.000<0.05. And there is a significant difference in the effect of training using Resistance Bands with an average increase of 6.46% and Stick Loads with an average increase of 47% on increasing front kick speed.